Abu Al Wared Revolution And The Idea Of Awaited Al Sufyanii - Alesa, Mohammad (European Scientific Journal, ESJ, 2017)
The idea of the Redeemer prevailed in most human civilizations, but in different forms. This, however, was coupled with a state of despair and the inability to change the reality. The idea was manifested in Islamic history through religious, tribal, and political determinants. Thus, it was one of the slogans of the Umayyad against the Abbasid authority to denounce their legitimacy in power. The Rebel, Abu Al Wared, used this slogan to establish the foundation of the revolution against the Abbasid power. Nevertheless, they realized its danger and took efforts to eliminate such danger before the spread of the revolution. Savior logo continued to be a way to convince the masses to revolt against authority for a long time, especially in the Abbasid era. In addition, it had a socio-economic determinant against feudal power on one hand and military power on the other hand.